Багатомовність особистості як необхідна умова життя в сучасному полікультурному світі - Леснянська-Дощак, Аліна (My University, 2018)
У статті узагальнено роль мовного розмаїття в концепції міжкультурної освіти. Проаналізовано поняття багатомовності, що полягає в оволодінні людиною двох і більше мов в певному суспільстві. Звернено увагу на історичні витоки становлення і розвитку понять «двомовність» і «багатомовність». З’ясовано умови, що сприяли розвитку багатомовної освіти та виховання в сучасному полікультурному світі. Констатовано причини, які увиразнили проблеми багатомовної освіти та навчання, а також вказано на шляхи їхнього розв’язання. Проаналізовано двомовну освіту її переваги та доцільність дослідження. Охарактеризовано мовну різноманітність у західноєвропейських школах та продемонстровано соціальні та освітні переваги багатомовності. Розкрито особливості формування комунікативної компетенції особистості, якій сприяють засвоювані учнем мовленнєві знання, вміння й навички, а також досвід між мовленнєвої взаємодії. З’ясовано необхідність мотивації учнів до вивчення кількох мов. Констатовано необхідність навчатися, жити і працювати в багатомовному мультикультурному середовищі, що унеможливлює цей процес без володіння належними мовленнєвими навичками щонайменше з двох іноземних мов. The role of linguistic diversity in the concept of multicultural education as well as the concept of multilingualism which consists in a person mastering two or more languages in a certain society have been regarded in the article. The attention is paid to the historical origin of the formation and development of the concepts "bilingualism" and "multilingualism". The analysis of bilingual education has been done and the following advantages of bilingual education have been distinguished: better understanding of other people, their culture and language, tolerance and open-heartedness, prospects on the world employment market, better quality of communication among different people and in different situations, greater interest to the native and foreign languages, creativity and originality of thinking, acceleration of personal development, deep cultural and genealogical roots. The linguistic diversity in Western European schools has been characterized and the social and educational benefits of multilingualism have been revealed. The peculiarities of the formation of the communicative competence of the individual have been defined and the factors promoting this formation have been singled out. They are as follows: learner's language learning, skills and abilities and the experience of the speech interaction. It has been found out that the need to study, live and work in a multilingual and multicultural environment involves having proper language skills in at least two foreign languages. It has been stated that multilingualism plays a leading role in today's European linguistic politics. Specialists from various science fields develop numerous constructive recommendations on teaching and learning foreign languages in a multicultural environment. The multilingual approach to learning is emphasized by the fact that in the process of individual’s language experience development the cultural context extends from the language within the family to a particular social group or other community, in particular school, university, community organizations, etc. That is the way the communicative competence of the individual is formed and promoted by the learner's acquired knowledge of the language, skills and abilities, as well as the experience of the speech interaction. Multilingualism is considered to be the process of the person’s use of several languages within the single state. The concept of social multilingualism as functioning of several languages with different or identical statuses in one state has also been characterized. Multilingualism exists in most countries of the world since at present different peoples and their languages interact with languages of other countries. There is also social multilingualism when there are several languages in the state with different or identical statuses. Different languages may coexist within a single society or even a family.
Keywords: багатомовність; особистість; двомовність; освіта; виховання; multicultural education; bicultural education; education